The factors that contribute to customer retention for Chevrolet in DRB-Hicom Berhad / Noor Aznina Naim - Naim, Noor Aznina (Faculty of Business and Management, 2006)
As market growth slows or as markets become more competitive and level of switching costs increase, firms are more likely to attempt to maintain their market share by focusing on retaining current customers. Customer retention has been advocated as an easier and more reliable source of superior performance. This research utilized a convenience methodology to improve customer retention, and the researcher has helped the firm identifying the factors that contribute to retain customer and initiate a variety of strategies to accomplish this objective. Four factors that contribute to retain customer that had been identify by researcher consists of long-term relationship, relationship commitment, trust and service quality.